Leaf Epidermal Comparison of Phasey Bean (Macroptilium lathyroides) and Siratro (Macroptilium atropurpureum) - I Made Saka Wijaya; Eniek Kriswiyanti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
Phasey bean (Macroptilium lathyroides) and siratro (Macroptilium atropurpureum) are introduced legumes that become a common species in pastureland. The nutritional content of these legumes has been explored, but on the contrary the anatomical study. The anatomical trait, especially in leaf epidermal, have been used to increase the understanding in taxonomy. This study aimed to investigate the leaf epidermal variability among phasey bean and siratro. The method used longitudinal section for upper and lower epidermal, then stained in safranin 0,1%. The results show that the upper epidermal in phasey bean have polygonal epidermal cell, while the lower part and the both part of siratro have irregular-shaped. The type of stomata in upper epidermal of phasey bean is paracytic and the lower epidermal is paracytic and anomocytic. Both epidermal sides in siratro have paracytic and anomocytic stomata. The index of stomata in phasey bean is higher than the siratro, but the index of trichomes in phasey bean is lower than siratro. The trichomes only absent in upper epidermal of phasey bean. Both plants have a similar types of trichomes: capitate glandular trichomes and linear non-glandular trichomes.